2008
DOI: 10.3928/01484834-20081101-07
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Among RN-to-BSN Distance Students Participating in Human Patient Simulation

Abstract: Simulation is a strategy increasingly being used to promote critical thinking skills among baccalaureate nursing (BSN) students. It has been used to a limited extent with RN-to-BSN students, many of whom take their educational program through distance delivery. The purpose of this qualitative study was to understand the critical thinking of distance RN-to-BSN students who participated in a simulation designed with interactive questions. Students taking the program, either by live televised broadcast (education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Reflection is defined as ''contemplation upon a subject, especially one's own assumptions and thinking'' (Scheffer and Rubenfeld 2000, p. 17). As a habit of mind, reflection enables students to gain insights into their own thinking for the purposes of deeper understanding and self-evaluation (Rush et al 2008).…”
Section: Critical Thinking Habits Of Mindmentioning
confidence: 99%
“…Reflection is defined as ''contemplation upon a subject, especially one's own assumptions and thinking'' (Scheffer and Rubenfeld 2000, p. 17). As a habit of mind, reflection enables students to gain insights into their own thinking for the purposes of deeper understanding and self-evaluation (Rush et al 2008).…”
Section: Critical Thinking Habits Of Mindmentioning
confidence: 99%
“…Specific examples of skills needed in mental health nursing that have been fostered through the use of simulation devices include critical thinking skills (Johannsson & Wertenberger 1996, Weis & Guyton‐Simmons 1998, Chau et al . 2001, Rush et al . 2008), communication skills (Donovan et al .…”
Section: Use Of Simulation In Mental Health Nursingmentioning
confidence: 99%
“…Concerning the inquisitiveness dimension, the most of the nursing students had positive disposition level; this finding is congruent with, Ali (2009) and Wangensteen et al (2010) This result might be related to, students activities that reality situation and uses techniques as role-playing and mannequins that help students to demonstrate critical thinking. In this regard, As well , Rush, Dyches, Waldrop, & Davis (2008) who stated that the simulation provoked inquisitiveness, application of standards, and thinking with intuitive processes supported by experience, interviews after simulations revealed that student confidence depended largely on experience with the type of scenario in the simulation.…”
Section: Discussionmentioning
confidence: 99%